SPYWARE AS BARRIER TO E-MARKETING: AN EMPIRICAL STUDY - Kumar , Dr. Satinder; Dubey, Rohit Kumar (LPPM Universitas Duta Bangsa Surakarta, 2023)
Present paper motive is to explore perceptions of customers towards Spyware issues in E-Marketing and their structural relationship to influence the perception. In present scenario E-Marketing is playing an essential part in Indian economy, especially where Prime Minister promotes cashless economy or online marketplace. Although E-marketing is one of the best modern and economical mediums for reaching out to new customers, although internet has created many advantages for the business but it has also brought many numerous risks. It would be wise to contemplate the various E-marketing ethical issues because innovative way of marketing has also lead to unethical practices as spyware problem. Spyware has been in controversy as it gets setup without knowledge and breaks the user’s privacy; even it has the potential to be misused. The study has revealed the customers have no control on their personal information as spyware leads to control the online user’s visits, collecting personal information and also misusing the same. Majority Customers are unaware regarding Spyware problems and they do not know how to handle with it. As the result the customers felt more Unsecure while transacting on the network because of their ignorance in this respect as SEM analysis has revealed that most of the variance in spyware is explained by two factors, Unsecure and Control. The results of the study are useful for the marketers as it would help them to frame comprehensive policy in relation to protect the personal information of customers so that they can feel safe and secure while buying online.